Chinese patients with p.Arg756 mutations of ATP1A3: Clinical manifestations, treatment, and follow‐up - Weihua Zhang; Jiuwei Li; Xiuwei Zhuo; Ji Zhou; Weixing Feng; Shuai Gong; Xiaotun Ren; Changhong Ding; Tongli Han; Fang Fang (Pediatric Investigation, 2022)
ABSTRACT Importance The phenotypes of ATP1A3 gene mutations are diverse. Relapsing encephalopathy with cerebellar ataxia and fever‐induced paroxysmal weakness and encephalopathy (FIPWE) are considered non‐classical phenotypes caused by p.Arg756 mutations of ATP1A3. Objective To summarize the clinical manifestations, treatment, and follow‐up of Chinese patients with p.Arg756 mutations of ATP1A3. Methods We analyzed the clinical features, treatment, and genotypes of eight children with p.Arg756 mutations of ATP1A3 who were treated in Beijing Children's Hospital from January 2014 to December 2019. Results Eight patients (six boys and two girls) were included; seven had been misdiagnosed with encephalitis. The age of onset ranged from 0.8 to 4.5 years. All patients had encephalopathy and had at least one episode of FIPWE. Cerebellar ataxia was present in nine episodes. Reversible splenial lesions of the corpus callosum were found in two patients in the acute phase. Three types of heterozygous ATP1A3 mutations were found: c.2267G > T (p.R756L) (patient 3 [P3]), c.2266C > T (p.R756C) (P2 and P4), and c.2267G > A (p.R756H) (P1, P5, P6, P7, and P8). Six mutations were de novo; two mutations were inherited. Both patients with p.R756C and one patient (P7) with p.R756H had four episodes of severe ataxia as the main manifestations. However, in the other three episodes, limb weakness was more prominent than ataxia. P5 with p.R756H exhibited overlap with FIPWE and rapid‐onset dystonia‐parkinsonism. Interpretation Acute encephalopathy followed by febrile disease was characteristic of the disease in patients with p.Arg756 mutations of ATP1A3. However, the weakness and ataxia were variable. Phenotypic crossover and overlap were observed among these patients.